2016
DOI: 10.1115/1.4034887
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Variations in the Dynamic Resistance Signature to Weld Strength in Resistance Spot Welding Using Principal Component Analysis

Abstract: Traditional quality control of resistance spot welds by analysis of the dynamic resistance signature (DRS) relies on manual feature selection to reduce the dimensionality prior to analysis. Manually selected features of the DRS may contain information that is not directly correlated to strength, reducing the accuracy of any classification performed. In this paper, correlations between the DRS and weld strength are automatically detected by calculating correlation coefficients between weld strength and principa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Consistently with the technological literature, 8,32 being the minimum point abscissa practically constant and the maximum point the landmark for the start of nugget formation (see also Section 2), we can state that the smaller the phase difference, and thus the larger the time interval between the local maximum and the end of the welding process, the more the heat energy supplied for nugget growth. Note that the inflection point typically located between the local minimum and maximum of the DRC (see, e.g.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Consistently with the technological literature, 8,32 being the minimum point abscissa practically constant and the maximum point the landmark for the start of nugget formation (see also Section 2), we can state that the smaller the phase difference, and thus the larger the time interval between the local maximum and the end of the welding process, the more the heat energy supplied for nugget growth. Note that the inflection point typically located between the local minimum and maximum of the DRC (see, e.g.…”
Section: Resultssupporting
confidence: 87%
“…6,31 The typical shape of a DRC acquired during this process is displayed in Figure 1 for illustrative purposes. In the light of Dickinson et al, 8 it mainly depends on physical changes induced in the material by the ongoing welding process and can be roughly outlined into five stages, as well depicted by Adams et al 32 For the sake of conciseness, these stages can be summarized as influenced by two main concurrent effects due to (a) the metal electrical resistivity and (b) the contact area among the metal sheets to joint. These effects develop during the RSW process by means of the heat produced by the current flow and the clamping pressure generated by copper electrodes.…”
Section: Technological Background and Data Structurementioning
confidence: 99%
“…We observe that the minimum point abscissa is practically constant among centroids of Figure 4. According to the technological literature, 8,32 the local maximum (NF) is the landmark for the start of the nugget formation (see also Section 2 and the typical DRC behavior depicted in Figure 1). Therefore, we can state that spot welds corresponding to DRC centroids with smaller phase difference (II) have larger time interval between the local maximum and the end of the welding process (IV), that is, larger exposition time to the heat energy supplied for nugget growth, and thus, larger nugget size.…”
Section: Resultsmentioning
confidence: 99%
“…We observe that the minimum point abscissa is practically constant among centroids of Figure 4. According to the technological literature, 8,32 the local maximum (NF) is the landmark for the start of the nugget formation (see also Section 2 and the typical DRC behavior depicted in Figure 1). Therefore, we can state that spot welds corresponding to Resistance…”
Section: Resultsmentioning
confidence: 99%
“…An important variable in the tissue hemostasis process is electrical impedance, which varies during the process due to the water content and cell structural change. Equivalent to the dynamic resistance in resistance spot welding [30][31][32], this dynamic impedance has been used as a signal to control the bipolar hemostasis process. V€ allfors and Bergdahl [33,34] suggested that the dynamic impedance during a bipolar vessel sealing process could be divided into several stages and tissue coagulation formed when the impedance reached the minimum.…”
Section: Introductionmentioning
confidence: 99%